The Reliability of Accretion Disk Inclination Derived from X-Ray Spectroscopy of Active Galaxies - Rong Du; Yuanze Ding; Luis C. Ho; Ruancun Li (The Astrophysical Journal, 2024)
The inclination angle of substructures in active galaxies gives insights into physical components from scales of the vicinity of the central black hole to the entire host galaxy. We use the self-consistent reflection spectral model RELXILL to measure the inclination of the inner region of accretion disks with broadband (0.3–78 keV) X-ray observations, systematically studying the reliability of this methodology. To test the capability of the model to return statistically consistent results, we analyze multiepoch joint XMM-Newton and NuSTAR data of the narrow-line Seyfert 1 galaxy I Zwicky 1 and the broad-line radio galaxy 3C 382, which exhibit different degrees of spectral complexity and reflection features. As expected, we find that adding more data for analysis narrows the confidence interval and that multiepoch joint observations return optimal measurements; however, even single-epoch data can be well fitted if the reflection component is sufficiently dominant. Mock spectra are used to test the capability of RELXILL to recover input parameters from typical single-epoch joint observations. We find that inclination is well recovered at 90% confidence, with improved constraints at higher reflection fraction and higher inclination. Higher iron abundance and corona temperature tighten the constraints as well, but the effect is not as significant as a higher reflection fraction. The spin, however, has little effect in reflection-based inclination measurements. We conclude that broadband reflection spectroscopy can reliably measure inner accretion disk inclination.